New petrographic and geochemical tracers for recognizing the provenance quarry of trachyte of the Euganean Hills, northeastern Italy. Issue 4 (7th December 2017) - Germinario, Luigi; Hanchar, John M.; Sassi, Raffaele; Maritan, Lara; Cossio, Roberto; Borghi, Alessandro; Mazzoli, Claudio
Abstract: Trachyte of the Euganean Hills is a subvolcanic porphyritic rock historically used as carving and building stone in northern and central Italy–primarily from Roman times onward–with the first evidence of its use dating back to prehistory. The numerous quarries and very similar trachyte varieties, as well as the widespread use of this stone, create several problems in defining its provenance for archaeological and historical materials. New petrographic and geochemical tracers for recognizing the provenance quarry of Euganean trachyte are presented here, providing a comprehensive reference database for archaeometric studies. The petrographic markers principally include quantitative data on mineralogical composition and textural features of phenocrysts and groundmass, determined by image analysis of chemical maps acquired by micro X‐ray fluorescence and scanning electron microscope‐energy‐dispersive X‐ray spectroscopy; particular use has been made of data on the abundance and grain‐size distribution of feldspar phenocrysts, phenocrysts‐groundmass ratio, content of SiO2 phases in the groundmass, and the arrangement and grain‐size of microlites in the matrix. The geochemical tracers involve composition of bulk rock and phenocrysts, determined by X‐ray fluorescence and laser ablation inductively coupled plasma mass spectrometry, respectively; quarry recognition can be achieved using plots built from concentrations of major and trace elements, with mineral‐scale chemistry being the most effective and precise discriminant property, especially in the case of biotite and, secondarily, augite, kaersutite, and magnetite.